2013
DOI: 10.1371/journal.pone.0078355
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus_Encoded LMP1 Upregulates MicroRNA-21 to Promote the Resistance of Nasopharyngeal Carcinoma Cells to Cisplatin-Induced Apoptosis by Suppressing PDCD4 and Fas-L

Abstract: Approximately 30% of patients with Epstein-Barr virus (EBV)-positive advanced nasopharyngeal carcinoma (NPC) display chemoresistance to cisplatin-based regimens, but the underlying mechanisms are unclear. The Epstein-Barr virus (EBV)-encoded latent membrane protein 1 (LMP1), a functional homologue of the tumor necrosis factor receptor family, contributes substantially to the oncogenic potential of EBV through the activation of multiple signaling pathways, and it is closely associated with a poorer prognosis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 59 publications
(86 reference statements)
0
61
0
Order By: Relevance
“…MIR155 is essential for LCL proliferation. EBV super-enhancers, enriched with EBNA2, EBNALP, and LMP1-activated NF-ÎșB subunits up regulate MIR155 and MIR21 expression in LCLs (Rosato et al, 2012; Yang et al, 2013). MIR21 regulates PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…MIR155 is essential for LCL proliferation. EBV super-enhancers, enriched with EBNA2, EBNALP, and LMP1-activated NF-ÎșB subunits up regulate MIR155 and MIR21 expression in LCLs (Rosato et al, 2012; Yang et al, 2013). MIR21 regulates PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-155 is upregulated by EBV infection (40,46), miR-21 is upregulated by EBV (40,47) and hepatitis C virus infection (48), and miR-17, miR-20, miR-96, miR-182, and miR-183 are upregulated, while miR-21, miR-99, miR-100, and miR-101 are downregulated by HCMV infection (41,(49)(50)(51).…”
mentioning
confidence: 99%
“…Among them was the research conducted by Meng et al 21 showed that PTEN (Phosphatase and tensin homolog) was a direct target of microRNA-21 that contribute to cell invasion. MicroRNA-21 contributes to apoptotic and chemotherapy resistance by directly targeting PDCD4 22 .…”
Section: Discussionmentioning
confidence: 99%